Sensitivity to the 0νββ decay of 136Xe and development of Machine Learning tools for pulse classification for the LUX-ZEPLIN experiment - Braz, Paulo Alexandre Brinca da Costa (2021)
Tese no âmbito do Doutoramento em Física, Astrofísica, apresentada ao Departamento de Física da Faculdade de Ciências e Tecnologia da Universidade de Coimbra.